EFFECT OF SEASON ON REPRODUCTIVE PERFORMANCE OF BUFFALOES AT AN ORGANIZED FARM - KHAN, H M; KHAN, H M; MOHANTY, T K; BHAKAT, M; RAINA, V S; GUPTA, A K (The Indian Journal of Animal Reproduction, 2023)
· Calving records of 773 Murrah buffaloes for the period from 2000 to 2007 at an organised farm ofNational Dairy Research Institute, Kamal, Haryana, India was analyzed to study the effect of season onreproductive performance traits of the herd. The overall Days open, Days to first service (DFS), Servicesper conception (SC), Breeding interval (Bl), Breeding interval between first and second service (Bl1 ),Breeding interval between second and third service (Bl2), Breeding interval between third·and fourth.service (Bl3), Breeding interval between fourth and fifth service (Bl4) and Breeding interval between fifthand sixth service (Bl5) of Murrah buffalo in the herd were found to be 170.32 ± 4.67, 91.89 ± 1.99, 2.05± 0.05, 74.70 ± 0.08, 73.57 ± 2.98, 82.96 ± 4.00, 67.68 ± 4.40, 72.63 ± 8.31 and 66.73 ± 13.69, respectively. Days open (183.13 ± 8.12} and breeding interval (80.78 days) were highest in wintercalvers. More services per conception were observed during rainy season (2.10 ± 0.08) and less during summer months (2.02 ± 0.12). Summer season calvers took more time in resumption of estrus cycle which resulted in longer time for days to first service (109.92 ± 5.28) as compared to other season,whereas opposite scenario was found in rainy season carvers (80.96 ± 2.59). The per cent heat detectionwas lower than 30% of the tabulated value signifying very severe problem in th~level of heat detectionin the herd. It can be concluded that heat detection should be improved to enhance the reproductiveefficiency of the herd.
Keywords: Heat detection; days open; breeding interval; service per conception; Murrah buffalo